2014
DOI: 10.4322/acr.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell neuroendocrine carcinoma of the esophagus: an autopsy case report

Abstract: Small-cell neuroendocrine carcinoma is a well-known aggressive neoplasia, which is usually associated with a poor prognosis. The lung is the most common primary site, but other organs may be involved, especially those of the digestive tract. The authors report the case of a 71-year-old Caucasian, male patient who was admitted because of congestive heart failure and loss of vision accompanied by right proptosis. Skull and sinuses computed tomography showed a tumoral mass involving the posterior region of the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[ 8 ] In 2016, Lyoda et al used etoposide plus cisplatin chemotherapy in a prospective clinical study diagnosed as LCNEC, and the results confirmed that the chemotherapy group was superior to the control group. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] In 2016, Lyoda et al used etoposide plus cisplatin chemotherapy in a prospective clinical study diagnosed as LCNEC, and the results confirmed that the chemotherapy group was superior to the control group. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%